A Concept of Philosophy in the Qur'anic Context (American Journal of Islam and Society, 1994)
One of the most debated subjects in philosophy is the nature andsubject matter of philosophy itself. It is pethaps the only discipline thatcritically discusses its own natum. This is one msan that has led philosophers,particularly after the nineteenth century, to distinguish philosophyfrom such other experimental sciences as physics, biology, or astronomy.When we add to this the nature of subjects discussed in philosophy, asopposed to the issues discussed in those sciences, the sharp distinctionbetween the two becomes decisively clear.It is our aim to investigate critically the nature of philosophical subjects,which constitub basically the method of philosophy, in order toarrive at a concept of philosophy that is acceptable to the Qur'anic perspective,which can be taken, as we shall see, as a contribution towardthe effort of Islamization. Our discussion requim the development of aclear conception of the term "philosophy." If we am to develop an Islamicconcept of philosophy, then we are required in the first instance toclarify what we mean by philosophy. We feel compelled to do this, becausein the history of human thought thew am more than a score ofconceptions about the nature, purpose, and subject matter of philosophy.However, settling this problem alone does not fulfill the task of our paper.We must, moreover, show what the role of philosophy may be in thissociety (in general) so that we can delineate mow effectively its significancein a Muslim community (in particular). Finally, we must try tojustify our arguments from the Qur'anic perspective in order to defendthe conception of philosophy that is to be developed hew as an adequateone.The discussion, then, will be divided into three main sections. Thefirst section will be devoted to "what philosophy is." In the second, weshall elucidate what we shall tern the "Qur'anic conception of or attitude ...